2017
DOI: 10.1016/j.jarmac.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Life Script Events and Autobiographical Memories of Important Life Story Events in Mexico, Greenland, China, and Denmark

Abstract: 1 This name uses Spanish naming customs; paternal last name is Zaragoza and maternal last name is Scherman. Please, use Zaragoza Scherman as the last name for citations. AbstractThe aim of this study was to test the cultural life script theory across four different cultures.We collected life scripts from 606 middle-aged and older adult participants in Mexico, Greenland, China, and Denmark, and examined whether key characteristics of life scripts generalize across these cultures. We also collected autobiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
65
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 34 publications
10
65
0
1
Order By: Relevance
“…This tendency was also indicated by Berntsen and Rubin (2004), although it seemed to be stronger in this study than in theirs. Whereas we can assume that the inclusion of more private social events in Japanese life scripts reflects the Japanese emphasis on cooperation and harmony, in view of the discussion of cultural differences in life scripts from the individualist/collectivist perspectives elucidated by Scherman et al (2017), additional investigation and data are needed to determine the existence and, if relevant, the cause of such differences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This tendency was also indicated by Berntsen and Rubin (2004), although it seemed to be stronger in this study than in theirs. Whereas we can assume that the inclusion of more private social events in Japanese life scripts reflects the Japanese emphasis on cooperation and harmony, in view of the discussion of cultural differences in life scripts from the individualist/collectivist perspectives elucidated by Scherman et al (2017), additional investigation and data are needed to determine the existence and, if relevant, the cause of such differences.…”
Section: Discussionmentioning
confidence: 99%
“…Ottsen and Berntsen (2014) investigated the life scripts of university students in Qatar and showed that some events were specific to Qatari students (i.e., mainly religious events), but concluded that there were many similarities among the life scripts of Qataris, Americans (Rubin et al, 2009), Danes (Berntsen & Rubin, 2004), and Turks (Erdo gan et al, 2008). Moreover, Scherman et al (2017), which included approximately 150 participants from each of four countries (Mexico, Greenland, China, and Denmark), found that some events were specific to each country but also concluded that there were many similarities across the four cultural life scripts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Se ha propuesto que la identidad requiere de la creciente semantización del funcionamiento de la memoria autobiográfica durante el ciclo vital (Piolino, Desgranges & Eustache, 2009), donde eventos personales recientes pueden tener más componentes episódicos en su reconstrucción, mientras que eventos remotos son reconstruidos con componentes más semánticos, llegando incluso a constituirse en esquemas o guiones de vida de momentos prototípicos, distintivos y emocionalmente significativos que resultan de interés para el 'sí mismo' o para otros (Berntsen & Rubin, 2002, 2004Janssen et al, 2011;Zaragoza-Scherman, Salgado, Shao & Berntsen, 2017). Se ha demostrado incluso que la actividad neuroanatómica y neurofuncional de la memoria autobiográfica varía a lo largo del ciclo vital cuando se reconstruyen recuerdos recientes o lejanos en el tiempo (Svoboda, Mckinnona & Levine, 2006;Markowitsch & Wezler, 2010).…”
Section: Semantización En La Memoria Autobiográfica E Identidadunclassified